2016
DOI: 10.1007/s00408-016-9935-7
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate-Induced Epithelial–Mesenchymal Transition in the Alveolar Epithelial Cell Line A549

Abstract: We have demonstrated that phenotypic changes of A549 cells induced by MTX are partly mediated by a TGF-β1-related intracellular signaling pathway, although TGF-β1 itself is not directly involved in this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 34 publications
5
22
0
Order By: Relevance
“…Reverse transcription of the total RNA into cDNA was performed using ReverTra Ace (TOYOBO, Osaka, Japan). Quantitative evaluation for indicated mRNA expression was performed by real-time PCR analysis using the CFX Connect™ Real-Time PCR Detection System (Bio-Rad Laboratories, Inc., Hercules, CA, USA) and the KAPA SYBR ® FAST qPCR Kit (NIPPON Genetics, Tokyo, Japan), as previously described (16). The primer sequences were as follows:…”
Section: Real-time Pcr Analysismentioning
confidence: 99%
“…Reverse transcription of the total RNA into cDNA was performed using ReverTra Ace (TOYOBO, Osaka, Japan). Quantitative evaluation for indicated mRNA expression was performed by real-time PCR analysis using the CFX Connect™ Real-Time PCR Detection System (Bio-Rad Laboratories, Inc., Hercules, CA, USA) and the KAPA SYBR ® FAST qPCR Kit (NIPPON Genetics, Tokyo, Japan), as previously described (16). The primer sequences were as follows:…”
Section: Real-time Pcr Analysismentioning
confidence: 99%
“…Several clinical reports suggested that MTX induces serious pulmonary side effects, such as pulmonary fibrosis . Recently, various efforts have been made to clarify the mechanism underlying MTX‐induced lung injury, showing the association with several factors including cytokine release, reactive oxygen species and epithelial‐mesenchymal transition . Nevertheless, the detailed mechanisms of MTX toxicity in the lungs are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, mRNA expression of some type II alveolar epithelial cell markers such as peptide transporter 2 (PEPT2) in H441 cells was higher than that in A549 cells, indicating that H441 would be a better alveolar type II epithelial cell model than A549. On the other hand, some reports suggested that MTX‐induced lung injury may be associated with epithelial‐mesenchymal transition (EMT) . In addition, EMT would occur in type II cells, but not in type I cells, in the lungs of patients with idiopathic pulmonary fibrosis and in human primary cultured alveolar type II epithelial cells .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations